The Effect of Employee Engagement and Leadership Style on the Performance of Gen Z Employees in Cirebon City with Innovative Behavior as a Mediation - Intan Permatasari; Muhamad Fadil Supriatna; Muhamad Alwi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the role of Innovation Behavior in mediating the influence of Employee Engagement and Leadership Style on the performance of Generation Z employees in the city of Cirebon. This is a quantitative study using Partial Least Square (PLS) testing based on Structural Equation Modeling (SEM) and primary data. The population of this study is Generation Z employees in Cirebon, with a sample of 100 Generation Z employees selected through Purposive Sampling. Data was obtained by distributing questionnaires online. Based on the results of the study, first, Employee Engagement has a negative but not significant effect on the performance of Generation Z employees. Second, Leadership Style has a positive but not significant effect on the performance of Generation Z employees. Third, Generation Z employees have a significant positive effect on the performance of Generation Z employees. Fourth, Employee Engagement has a significant positive effect on Innovation Behavior. Fifth, Leadership Style has a significant positive effect on Innovative Behavior. Sixth, Innovative Behavior has a significant positive effect in mediating Employee Engagement on Generation Z Employee Performance. Seventh, Innovative Behavior has a positive but not significant effect in mediating Leadership Style on Generation Z Employee Performance. This study indicates that by paying attention to and providing work interest along with leadership that adapts to each employee's generation, it can encourage innovative behavior to enhance their performance.